The Effect of Online Learning in Developing English Speaking Skills - Alshammari, Muteerah Bunayan (Journal of Educational and Psychological Sciences, 2022)
The COVID 19 pandemic has affected all aspects of the life, including the education system. Online learning appears to be efficient in several subjects, including English as a Second Language (ESL). The purpose of this study is to prove through a review of previous research that distance learning helps ESL learners in Saudi Arabia to practice English and develop their speaking skills more efficiently than being in an offline classroom setting. This study reviews up-to-date studies related to the importance of online lessons in developing speaking skills for ESL learners. The study illustrates the difficulties students face in offline classes that prevent them from participating in English discussions; discusses the importance of online learning in developing English speaking skills; and 3) provides suggestions that will help ESL learners to speak English fluently.